From limbs to leaves: common themes in evolutionary diversification of organ form - Mentink, Remco A.; Tsiantis, Miltos (Frontiers in Genetics, 2015)
An open problem in biology is to derive general principles that capture how morphogenesis evolved to generate diverse forms in different organisms. Here we discuss recent work investigating the morphogenetic basis for digit loss in vertebrate limbs and variation in form of marginal outgrowths of angiosperm (flowering plant) leaves. Two pathways underlie digit loss in vertebrate limbs. First, alterations to digit patterning arise through modification of expression of the Patched 1 receptor, which senses the Sonic Hedgehog morphogen and limits its mobility in the limb bud. Second, evolutionary changes to the degree of programmed cell death between digits influence their development after their initiation. Similarly, evolutionary modification of leaf margin outgrowths occurs via two broad pathways. First, species-specific transcription factor expression modulates outgrowth patterning dependent on regulated transport of the hormone auxin. Second, species-specific expression of the newly discovered REDUCED COMPLEXITY homeodomain transcription factor influences growth between individual outgrowths after their initiation. These findings demonstrate that in both plants and animals tinkering with either patterning or post-patterning processes can cause morphological change. They also highlight the considerable flexibility of morphological evolution and indicate that it may be possible to derive broad principles that capture how morphogenesis evolved across complex eukaryotes.